Category shifts used in the english - Indonesian translation of " Facebook and Google criticised by George Soros " in BBC News - Rexy Ade Irawan (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2018)
wt,1./ws.c.1